PENGARUH PERUBAHAN TINGGI HAK TERHADAP VOLUME KAKI DI HITUNG DARI SHOE LAST - Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2015)
Shoes is a footwear consisting of a sol, right, hood, strap, and tongue. High heels become one of the main attraction for women due to wearing high heels can support the appearance of a woman. High-heeled shoes have several sizes and shapes. A shoemaker should take into calculate the volume of the foot while making shoes. The higher the heel is used, then the assumption of the volume of the foot will change as well. How big is the change in the volume of the foot which in this case is represented by the shoe last as the coppier to change shoes high heels become into research questions. The author in this case chose the title "Effect Of Heel Height Change In Leg Volume Calculated From Shoe Last". Volume calculations performed on the test specimens in the form of shoe last measuring 37 standard models and taper at the heel height 1, 3, 5, and 7 with specimens amount 3 pieces for each size. Volume measurements performed by the method of measurement of static and dynamic volumes. Static measurement using the weighing technique to obtain the speci Dynamic calculations by measuring the volume using a measuring tool. Research data showed a linear equation for the volume of each test specimen: static calculations; y = 0,0194x + 553.16 (size 37 standard models); y = 0,0065x + 564.75 (size 37 models taper). For dynamic calculation: y = 0,1033x + 552.12 (size 37 standard models); y = 0,0033x + 563.4 (size 37 models taper). High heel changes does not significantly influence the volume of the foot, which is calculated from the shoe last as foot replica in high heel with a different size, the volume is calculated as static or dynamic.